2010
DOI: 10.1089/met.2009.0053
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Criteria for Metabolic Syndrome: Caucasians Versus African-Americans

Abstract: If diagnosis of metabolic syndrome is intended for early recognition of CVD risk and slowing CVD development, current definitions for metabolic syndrome will not capture healthy AA. Health-care providers may consider assessing percent body fat and participation in regular exercise, because these criteria would help identify AA at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…This ethnic difference was also documented by Zeno et al (2010), who showed that differences do exist between people of European ancestry and African Americans in terms of diagnostics for MetS and also for risk factors, as African Americans have a favourable lipid profile compared to people of European ancestry. One potential limitation of the study is non-estimation of fasting glucose, due to which MetS might be under-estimated.…”
Section: Discussionmentioning
confidence: 54%
“…This ethnic difference was also documented by Zeno et al (2010), who showed that differences do exist between people of European ancestry and African Americans in terms of diagnostics for MetS and also for risk factors, as African Americans have a favourable lipid profile compared to people of European ancestry. One potential limitation of the study is non-estimation of fasting glucose, due to which MetS might be under-estimated.…”
Section: Discussionmentioning
confidence: 54%
“…Increases observed in all measures of adiposity in overweight traders also (with prevalence of 33.0%) compared with normal weight traders in our study suggest that most of the traders (56.4%) are at risk of CVD. There is therefore an urgent need for early diagnosis of MS as well as modulation diet and lifestyles to prevent the burden of non-communicable diseases [20] especially in Nigerians who are blacks with known higher prevalence of metabolic diseases than Caucasians [5].…”
Section: Discussionmentioning
confidence: 99%
“…Visceral adiposity has been reported as the most common cause of insulin resistance and a powerful aetiopathogenic factor for the development of type 2 diabetes mellitus (DM2) and accelerated atherogenesis [3]. MS is the concurrence of disturbed glucose and insulin metabolism, overweight and abdominal fat distribution, mild dyslipidaemia, and hypertension associated with subsequent development of DM2 and cardiovascular disease (CVD) [2,4,5]. The prevalence of metabolic syndrome has been reported globally and is thought to affect Nigerians [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Caucasian populations, African Americans with lower CRF levels tend to have a worsened CVD risk profile (hypertension, obesity, insulin resistance, and elevated inflammation) [9, 10, 3335]. Further, the few data evaluating CRF and mortality by race suggest that CRF is an important risk factor for mortality in both African American and Caucasian adults.…”
Section: Mortality Risk Reduction By Crf In African American and Cmentioning
confidence: 99%